The legal framework of cybercrime in Palestine - Elshobake, Mohammed R. M.; Laeba, Muhammad (Brill Publishers, 2021)
The rate of committing cybercrimes in Palestine has increased in recent years due to the increased use of the Internet and social media, in addition to the absence of deterrent legislation to combat these crimes. Palestine suffers from legal problems in the field of criminal legislation due to the duplication of penal laws applied in the West Bank and Gaza Strip. This paper will discuss the legal framework of cybercrimes in Palestine. The researcher will mainly use historical, analytical, and library research methods for this purpose. The results indicate that the legal framework regulating cybercrimes in Palestine is not unified, and the difference in legislation regulating cybercrimes in Palestine has led to different penalties for cybercrimes, which violates the principle of equality stipulated in the Palestinian Basic Law (Palestinian Interim Constitution). The benefit of this paper is to propose some recommendations to develop Palestinian laws in order to combat cybercrimes.